Collective Reasoning of Cirebon’s Petatah-petitih in the COVID-19 Pandemic Era - Iffan Ahmad Gufron; Jajat Darojat; Barnawi Barnawi (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2022)
The local wisdom-based Cirebon's Petatah-petitih, namely Slaman, Slumun, Slamet, and Slata, Slutu, Wutuh, has played an important role in shaping people's mindsets, especially during the COVID-19 pandemic. This paper is a philological study of copies of manuscripts about Jawokan and Suluk still practiced by the people of Cirebon. The paper aims to discuss the contextual problems of COVID-19 from the perspective of oral literature that has developed in Cirebon. Using a qualitative-descriptive approach, this study will examine the oral literature of Cirebon's Petatah-petitih through Abed al-Jabiri's critique of reason named burhānī. The study found that the ideas formed in Cirebon's Petatah-petitih could be a power of knowledge in dealing with the COVID-19 pandemic. Later, it will use Michel Foucault's theory of the relationship between power and knowledge as an analytical framework. In this regard, the meaning of something is always found in relation to other meanings. The value of Cirebon's Petatah-petitih will be meaningful and have life value if it is applied to deal with the recent pandemic.